Dental manifestations and treatment of hypophosphatemic rickets: A case report and review of literature - Xinyang Jin; Yuedan Xu; Wei Liu; Zhiwei Shi; Yi Sun; Xinni Pan; Ling Zhang; Baiping Fu (Nature Publishing Group, 2023)
Abstract Background The treatment and management of patients suffering from hypophosphatemic rickets (HR) remain a major challenge for dental practitioners and affected patients. Objectives To report a case of HR presenting with specific dental findings and to review the dental manifestations and treatment of HR patients. Methods Case: A 32-year-old male presented with multiple dental abscesses and short stature. A thorough history was taken followed by clinical oral examination, and relevant radiological investigation was done. Literature research: In 2020, electronic literature searches were carried out in PubMed and complemented by a careful assessment of the reference lists of the identified relevant papers. Articles and reports fulfilled the inclusion criteria: indexed reviews, case series and case reports in English and restricted to human studies were considered. Results The intraoral examination revealed multiple dental abscesses and general periodontal disease; the radiographic examination showed poorly defined lamina dura, large pulp chambers and periapical lesions. Based on the contents of the 43 articles identified in the search, the current knowledge of dental manifestations, treatment and management of HR was summarized. Conclusions As HR is a multisystem disease, multidisciplinary care is needed. By summarizing current evidences, we proposed an evidence-based dental management and provided recommendations on diagnosis and treatment of the disease. It is of profound clinical significance to acquire knowledge of the dental manifestations and provide optimal treatment options for patients.